Single center, retrospective evaluation of requiring 48 hours versus 24 hours before a pharmacist-driven protocol-based IV to PO conversion of azithromycin - Abraham Felix; Winifred Pardo; Wilbert Fuerte; Laura Morales; Timothy P. Gauthier (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
Shortening a pharmacist-driven policy to allow a switch from IV to PO azithromycin after 24 hours instead of 48 hours led to 26% increase in oral azithromycin days of therapy (P < 0.001) and was associated with a shorter length of stay.